Student’s Mathematics Ability in Written Communication Based on Van Hiele's Theory and Gender - Alfiani Athma Putri Rosyadi; Yus Mochamad Cholily; Abdul Latief; Siti Salina Mustakim (Hipotenusa: Journal of Mathematical Society, 2025)
The student's ability to express and understand mathematical ideas in writing; Whether in tables, formulas, diagrams, drawings, or demonstrations, is called the student's written mathematical communication skills. Van Hiele's theory divides students' development in learning geometry into five levels, namely from level 0 to level 4. The purpose of this study is to find out students' mathematics ability in written communication based on Van Hiele's theory which is reviewed from gender differences. This research is a qualitative descriptive research. Students' mathematical communication skills at level 4: (1) can visually classify flat shapes, (2) can describe flat shapes visually, (3) can show the characteristics of flat shapes through pictures, (4) can write the relationships of concepts on flat shapes well, (5) can write how to determine the area and circumference of flat shapes, (6) can use terms and notation to present data. Meanwhile, level 1 students are still not able to describe the shapes of flat buildings visually well and are not able to write down the relationship of concepts on flat buildings well. In addition, related to gender, some aspects are superior to men and others are superior to women.